Common and Uncommon Imaging Presentations of Ectopic Pregnancy. (1st July 2022) - Schallert, Kellan; DeAngelis, Gia; Krishnaraj, Arun
Abstract : Ectopic pregnancy most commonly occurs in a fallopian tube (~95%1 ) (Figure 1 ). Major risk factors for ectopic pregnancy include a history of pelvic inflammatory disease or previous tubal surgery. Additional risk factors include smoking, assisted reproductive technology, and the use of an intrauterine device.2 Ectopic pregnancies located outside the fallopian tube have a poorer prognosis, as they have more blood supply, grow larger, and have an elevated risk of catastrophic hemorrhage if ruptured. The clinical presentation of pelvic pain, elevated β-human chorionic gonadotropin, and vaginal bleeding is similar, regardless of the location of an ectopic pregnancy; thus, imaging plays a crucial role in directing management. Early diagnosis by imaging has played a key role in reducing maternal mortality and allowing patients to pursue more conservative management options to reduce morbidity and preserve future fertility. However, ruptured ectopic pregnancy still remains the leading cause of maternal death in the first trimester.3 Uncommon locations of ectopic pregnancy often are missed or incorrectly diagnosed at initial imaging, resulting in poor outcomes.